A polydimethylsiloxane coating to minimize weathering effects on granite. (15th October 2016) - Kronlund, Dennis; Lindén, Mika; Smått, Jan-Henrik
Graphical abstract: Highlights: A sprayable water-repellent PDMS coating is developed for granite protection. The impact of UV- and water-based weathering mechanisms on granite is studied. The PDMS coatings display great stability in all the studied weathering tests. Degradation effects of pore salt crystallization is eliminated with a PDMS coating. Abstract: The impact of common weathering mechanisms on granite has been elucidated. A sprayable polydimethylsiloxane (PDMS) solution and a commercial reference coating formulation (Faceal Oleo HD) have been applied on granite to produce durable surface coatings that minimize weathering effects. Sufficiently thick PDMS coatings display superior stability in all the studied weathering tests when compared to the reference coating, as the impact of weathering on the hydrophobic functionality of the PDMS-coated samples is minimal. Furthermore, due to the excellent water and salt blocking behavior of PDMS, the PDMS-coated stones display an overall better stability against weathering compared to untreated stones.